2000
DOI: 10.1111/j.1499-1654.2000.001592.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Retention Rates of Lamotrigine, Gabapentin, and Topiramate in Chronic Epilepsy

Abstract: The impact of these new antiepileptic drugs on the long-term course of chronic partial epilepsy is likely to be small, as approximately three of four patients will discontinue therapy. More patients appear to continue on TPM compared with LTG or GBP, with a possible reason being better perceived efficacy of TPM, despite having the highest incidence of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…This finding was in contrast to what was found by SANAD study, in which valproate and topiramate showed same treatment failure rate as a result of LE. In addition, our study showed that the LE, rather than AE is the most frequently precipitant for the discontinuations of SRVPA and topiramate, which is not consistent with other reports [12], [17], [20]. Compared with those studies, our study employed lower initial dosages and slower titration, and had longer time of follow-up.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This finding was in contrast to what was found by SANAD study, in which valproate and topiramate showed same treatment failure rate as a result of LE. In addition, our study showed that the LE, rather than AE is the most frequently precipitant for the discontinuations of SRVPA and topiramate, which is not consistent with other reports [12], [17], [20]. Compared with those studies, our study employed lower initial dosages and slower titration, and had longer time of follow-up.…”
Section: Discussioncontrasting
confidence: 95%
“…It was assumed that the treatment failure for SRVPA and topiramate were 25% and 35% after one year, respectively [16], [17]. In this study, SRVPA was considered as an active comparator, there needed 415 patients for each group to achieve 90% power (β = 0.1) at a 0.05 significance level to detect an equivalence hazard ratio of 1.35, assuming a dropout rate of 20% for both groups during the whole study.…”
Section: Methodsmentioning
confidence: 99%
“…As such, medication retention is considered one of the most relevant measures of the overall performance of an antiepileptic drug. 4749 While medication retention has historically been measured as the proportion of patients continuing therapy at a set time point following treatment initiation, examining more detailed components of drug retention as we did here, may provide insights into specific aspects of a drug’s performance. For example, we found similar proportions of patients resuming therapy after treatment discontinuation, indicating that the tolerability of the two drug groups are likely comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Selection bias could not be avoided in comparing effectiveness of AEDs in clinical practice. Therefore potential confounding factors should be excluded in using Cox regression model during multivariate analysis, allowing for a more scientific comparison of different AEDs [ 18 , 33 ]. Cox proportional hazards models (95% confidence interval [CI]) were employed to analyze the hazard ratios (HRs).…”
Section: Methodsmentioning
confidence: 99%